2018
DOI: 10.1002/anie.201802650
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Anion Binding Properties of Electron‐Deficient Tetrahomocorona[4]arenes: Shape Selectivity in Anion–π Interactions

Abstract: Tetrahomocorona[2]arene[2]tetrazines were constructed by means of a fragment coupling strategy based on nucleophilic aromatic substitution reaction starting from 3,6-dichlorotetrazine and o-, m-, and p-bis(hydroxymethyl)benzenes. The unprecedented macrocycles gave rectangular box-like cavities with tunable cavity sizes and deficient electronic properties depending on the substitution pattern of phenylene. Due to anion-π interactions, they formed complexes selectively with azide and thiocyanate owing to complem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 74 publications
0
49
0
Order By: Relevance
“…However, in a medium of high Cl − concentration (0.10 M), such as the one we adopted for our measurements, the ability of the ligand chains to form hydrogen bonds with ClO 4 − and PF 6 − is lower than in pure water due to saturation with Cl − . As a matter of fact, the free energy changes (−12.0 to −13.7 kJ/mol) for ClO 4 − and PF 6 − binding by L3 (protonated and not-protonated) fall near, or slightly above, the upper limit (−12.0 kJ/mol) previously found for anion–π interactions in water [12,13,14], suggesting that some hydrogen bonding of the anion with chain protons is still active, while the free energy changes (−6.3 to −9.1 kJ/mol) for ClO 4 − binding by L4 (protonated and not-protonated) are close to the lower limit (−8.6 kJ/mol) in agreement with the loss of such a hydrogen bonding contribution.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…However, in a medium of high Cl − concentration (0.10 M), such as the one we adopted for our measurements, the ability of the ligand chains to form hydrogen bonds with ClO 4 − and PF 6 − is lower than in pure water due to saturation with Cl − . As a matter of fact, the free energy changes (−12.0 to −13.7 kJ/mol) for ClO 4 − and PF 6 − binding by L3 (protonated and not-protonated) fall near, or slightly above, the upper limit (−12.0 kJ/mol) previously found for anion–π interactions in water [12,13,14], suggesting that some hydrogen bonding of the anion with chain protons is still active, while the free energy changes (−6.3 to −9.1 kJ/mol) for ClO 4 − binding by L4 (protonated and not-protonated) are close to the lower limit (−8.6 kJ/mol) in agreement with the loss of such a hydrogen bonding contribution.…”
Section: Resultsmentioning
confidence: 88%
“…As for supramolecular chemistry, electronic features of s-tetrazine, such as a positive quadrupole moment, a high molecular polarizability, dispersion forces, or even electron sharing, have recently inspired the possible use of this heteroaromatic ring as a functional group to bind anions, an assumption that found solid foundations on ab initio calculations [2,3,4,5] and on the experimental evidence that anion– s -tetrazine ring interactions play an active role in determining the architecture of some metalla-macrocycles [6,7]. More recently, it was shown that s -tetrazine rings do behave as a binding site for anions even in solution [8,9,10,11,12], the anion– s -tetrazine interaction emerging as a promising tool for the construction of anion receptors as well as for the self-assembling of anion coordination frameworks (ACF) and polymers (ACP) [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Thea cquired tetrahomocorona [2]arene [2]tetrazines 8-11 displayed interesting photophysical and electrochemical properties.I nU V/Vis spectra recorded in acetonitrile solution, they gave three absorption bands at l max = 269-271, 342, and 523-529 nm with molar extinction coefficients (e)b eing (1.8-2.5) 10 3 ,( 5.0-6.9) 10 3 ,a nd (1.0-1.4) 10 3 mol À1 cm À1 , [26] respectively (Supporting Information, Figure S1). The absorption bands at the longest wavenumbers were attributable to the n!p*t ransitions of the tetrazine chromophores.…”
mentioning
confidence: 67%
“…Multifarious macrocyclic receptors bearing preorganized cavities and multiple noncovalent binding sites are the leading workhorses since the birth of host–guest and supramolecular chemistry. [ 1–9 ] No matter naturally occurring or wholly artificial synthetic, supramolecular macrocyclic entities not only contribute to the fundamental research of molecular recognition, [ 3,4 ] but also have established a variety of functional applications, such as molecular machines, functional stimuli‐responsive assemblies, energy storage devices, adsorption/separation materials, etc. [ 5–7 ] Among them, macrocyclic arenes obtained from phenol‐aldehyde chemistry, for example calix[n]arenes, pillar[n]arenes, and their derivatives, are undoubted the milestones of synthetic macrocyclic chemistry, [ 1f,8d ] and have also unleashed unlimited inspirations for the design and exploitation of new polyphenolic macrocycles.…”
Section: Methodsmentioning
confidence: 99%